Cross-Atlantic modification and validation of the A Tool to Assess Quality of Life in Idiopathic Pulmonary Fibrosis (ATAQ-IPF-cA). Issue 1 (14th May 2014) - Yorke, Janelle; Spencer, Lisa G; Duck, Annette; Ratcliffe, Sarah; Kwong, G NgMan; Longshaw, Mark S; Belkin, Amanda; Swigris, Jeffrey J
Abstract : Rationale: The A Tool to Assess Quality of Life in Idiopathic Pulmonary Fibrosis (ATAQ-IPF) was developed in the USA to assess health-related quality of life in patients with IPF. It is likely that some of the original ATAQ-IPF items perform differently when applied in different countries. This paper reports results of a study conducted to identify the need to refine the content of the ATAQ-IPF to minimise cross-country bias between the USA and the UK. Methods: The ATAQ-IPF and other study measures were completed by patients attending specialist IPF clinics in the USA and UK. Rasch analysis was used to determine which items performed differently across countries (USA vs UK) and refine the original ATAQ-IPF to an instrument without cross-country bias (ATAQ-IPF-cA). Preliminary validation of the modified instrument was examined by assessing correlations between ATAQ-IPF-cA scores and scores from dyspnoea-specific patient-reported outcome (PRO) measures. Results: 139 patients with IPF (USA=74; UK=65) participated in the study. A total of 41 items and 4 domains were removed from the original, 86-item instrument to yield the 43 items and 10 domains of the ATAQ-IPF-cA. Each domain had good fit to the Rasch model, internal consistency was comparable to the corresponding domains for the original ATAQ-IPF, and validity was supported by significant correlations between its scores and scores from dyspnoea-specific PROs. Conclusions: The reliability and validity of the substantially shortened ATAQ-IPF-cA are acceptable and comparable to the original instrument. We recommend use of the ATAQ-IPF-cA in IPF studies in which participants are enrolled from the USA and UK.